Pilot study on 11C-CFT dynamic imaging using total-body PET/CT: biodistribution and radiation dosimetry in Parkinson's disease - Xin, Mei; Li, Lianghua; Wang, Cheng; Shao, Hongda; Liu, Jianjun; Zhang, Chenpeng (Frontiers in Neurology, 2023)
Objective Total-body PET/CT equipment, uEXPLORER, is a newly developed imaging technology with a superior resolution, high sensitivity, and high signal-to-noise ratio, providing unique application advantages in the pharmacokinetic evaluation of positron tracers. While 11C-CFT PET/CT has been widely utilized in the early diagnosis of Parkinson's disease (PD), it is limited by the short half-life of the radionuclide and an incomplete understanding of its biological distribution in humans. This study aimed to use a total-body PET/CT dynamic scan with 11C-CFT imaging to describe the real-time internal biodistribution in PD patients and to obtain accurate radiation dosimetry. Methods Six male subjects with suspected PD underwent dynamic 11C-CFT total-body PET/CT. Following a bedside intravenous bolus injection of 373.3 ± 71.56 MBq of 11C-CFT, PET acquisition was performed synchronously for 75 min with a maximum axial field of view (AFOV) of 194 cm. Time-activity curves (TACs) were generated by delineating volumes of interest (VOIs) of the sourced organs using PMOD software. Tracer kinetics and cumulative organ activities were calculated, and absorbed doses were calculated and estimated using the OLINDA/EXM software. Results In the systemic TAC analysis of 11C-CFT, several unique types of distribution patterns were obtained among several major organs, including a “Fast-in Fast-out” pattern in the kidneys, lungs, spleen, and thyroid, a “Fast-in Slow-out” curve in the heart wall, a “Slow-in Slow-out” mode in the liver, a “Low-level extending” pattern in the whole brain and muscle, and a “Slow-in to plateau” trend in the striatum and bone. The effective dose of 11C-CFT was calculated to be 2.83E-03 mSv/MBq, which is only one-third of the literature value measured by the conventional method. Moreover, this dose is much lower compared to all other doses of DAT radioligands used in PET imaging. Conclusion This study is a pioneering application of total-body PET/CT to 11C-CFT dynamic imaging. Our results confirmed that 11C-CFT has a favorable total body biodistribution, an extremely low internal radiation dose, and high imaging quality, making it suitable for reasonable PD diagnosis in patients requiring multiple follow-up examinations.